Multinational alliances: A note on the perception of technology executives - Prasad, S. Benjamin (International journal of value-based management, 1995)
Multinational alliances in the 1980s came into vogue as one of the prominent instruments of corporate strategies. In the process of forging alliances, especially in the technologyintensive firms, senior technology executives such as directors of R & D often play a vital advisory role. This short paper reports the findings of survey of American technology executives. Among the findings two are noteworthy in the conceptualizations of multinational alliances: Alliances are viewed as a means to solving a firm's strategic problems, and as offering mutual learning opportunities, rather than “win-win possibilities” for firms entering the alliances.